Why people need privacy? The role of privacy fatigue in app users' intention to disclose privacy: based on personality traits. Issue 4 (13th August 2020) - Tang, Jie; Akram, Umair; Shi, Wenjing
Abstract : Purpose: Mobile Applications (App) privacy has become a prominent social problem. Compared with privacy concerns, this study examines a relatively novel concept of privacy fatigue and explores its effect on the users' intention to disclose their personal information via mobile Apps. In addition, the personality traits are proposed as antecedents that will induce the personal perception of privacy fatigue and privacy concerns differently. Design/methodology/approach: Data were collected from 426 respondents. Structure equation modeling was used to test the hypotheses. Findings: The findings describe that App users' intention toward personal information disclosure is determined by privacy fatigue and privacy concerns, but the former has a greater impact. With minor exceptions, the two factors are also influenced by different personality traits. Specifically, neuroticism has positive effects on privacy fatigue, but agreeableness and extraversion have presented the opposite results on the two variables. Practical implications: This research is very scarce to examine the joint effects of privacy fatigue, privacy concerns and personality traits on App users' disclosing intention. In doing so, these results will be of benefit to App providers and platform managers and can be the basis for a variety of follow-up studies. Originality/value: While previous research just focuses on privacy concerns, this study explores the critical roles of privacy fatigue and opens up a new avenue of emotion-attitude analysis that can further increase the specificity and richness of users' privacy research. Additionally, implications for personality traits as antecedents in the impact of App users' privacy emotions and attitudes are discussed.